Cylinder gas distribution type two-stroke engine - YUTING ZHENG (2007)
A two-stroke engine of cylinder valve actuating type is prepared as forming valve actuating mechanism by one work cylinder and a numbers of valve actuating cylinders, connecting two types of said cylinders in parallel way and setting air door between them, arranging air channel at top of valve actuating cylinder and air inlet of work cylinder at one side of combustion chamber for coordinating it with air outlet through air door and valve actuating cylinder, setting air exhaust of work cylinder at middle part of work cylinder and setting link piston of both said cylinders on the same crank shaft.